Physiological monitoring of tissue pH: In vitro characterisation and in vivo validation of a quinone-modified carbon paste electrode. (1st March 2019) - Herdman, Karen M.; Breslin, Carmel B.; Finnerty, Niall J.
Abstract: The fluctuation of physiological pH from homeostatic levels has the potential to cause life threatening complications unless counteracted in a timely manner. Therefore, the development of reliable and accurate sensors for the continuous monitoring of pH is of vital importance for clinical monitoring. Herein, we describe the extensive in vitro characterisation of a quinone-modified carbon paste electrode (CPE) and its subsequent in vivo validation in the peripheral tissue of anaesthetised rats. Sensocompatibility investigations identified stable and accurate measurements in lipid (phosphatidylethanolamine; PEA) and protein (bovine serum albumin; BSA) solutions when the pH sensor was continuously cycled for nine hours in the physiological contaminants. The influence of endogenous electroactive molecules e.g., ascorbic acid and uric acid and pharmacological interferents e.g., acetaminophen and acetylsalicylic acid was deemed negligible on the pH sensitive peak. Furthermore, there was no impact of ionic strength and the quinone oxidation peak remained selective for H + over other endogenous cations. The effect of temperature and a pseudo reference electrode (PRE) on the sensor performance have also been elucidated. The efficacy of the modified-CPE to respond to in vivo tissue pH dynamics was demonstrated using a model of peripheral ischaemia and sodium bicarbonate injections. Collectively, this body of evidence clearly support the ability of the quinone-modified CPE to continuously measure pH fluctuations under physiological conditions. Graphical abstract: Highlights: Stable recordings in proteins, lipids and endogenous interferents are reported. Sensor performance maintained in varying ionic strength and cation concentrations. Influence of temperature and pseudo reference electrode are elucidated. Sensor response to decreasing and increasing pH reported in anaesthetised rat.